P00117 Explaining the survival disadvantage for men with non-small-cell lung cancer (NSCLC) compared with women in Osaka, Japan. (July 2015) - Li, R.; Ito, Y.; Ioka, A.; Nakayama, T.; Rachet, B.
Abstract : Background: Survival from non-small-cell lung cancer (NSCLC) is much higher for women than for men in Japan. We adapted methods from the causal inference setting using routine population-based cancer registry data to examine what proportion of the difference in survival can be explained by diagnostic and treatment factors. Methods: 34 161 patients were diagnosed with NSCLC between 1993 and 2004 in Osaka, Japan, and followed up for at least 5 years. We regarded patients with localised cancer as being diagnosed early and with regional or distant spread as diagnosed late. G-computation procedures were used to estimate the proportion of the effect of sex on survival mediated by stage and by treatment, controlling for sociodemographic factors. Findings: There were substantial sex differences in NSCLC net survival (at 1 year 47% for men versus 53% for women; 5 years, 17% versus 24%). Men were less likely to be diagnosed at an early stage (22% men diagnosed early versus 28% women, OR 0.75 [0.71–0.80], p < 0.001). They were less likely to receive curative treatment than women (20% men versus 24% women, 0.82 [0.78–0.87], p < 0.001), especially for those with localised stage (61% versus 69%, 0.72 [0.65–0.80], p < 0.001). Preliminary results from g-computation procedures show that 20% of the effect of sex on 1-year survival was mediated by stage, and 40% by treatment. Interpretation: Late presentation and less curative treatment contribute to the survival disadvantage in men. Disentangling this disadvantage by treatment and stage informs us what could be done to most effectively reduce the inequality in outcome.